1997
DOI: 10.1364/ol.22.001344
|View full text |Cite
|
Sign up to set email alerts
|

Autocorrelation measurement of 6-fs pulses based on the two-photon-induced photocurrent in a GaAsP photodiode

Abstract: We experimentally characterize the two-photon response of a GaAsP photodiode by use of a femtosecond Ti:sapphire laser tuned below the diode bandgap. The photodiode is shown to be highly suitable for real-time second-order autocorrelation measurements of pulses as short as 6fs in duration and with energies as small as a few picojoules.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
111
1
2

Year Published

2003
2003
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 218 publications
(116 citation statements)
references
References 12 publications
2
111
1
2
Order By: Relevance
“…For a GaP photodector, the maximum sensitivity for a one photon process was known to be Sone photon ~ 1 × 10 -1 mA/mW at 430 nm [24], which is three orders higher than that for the two photon process. The two photon sensitivity for the GaP photodiode is comparable to the previous report for GaAsP photodiode by the same order of magnitude [4,17]. Note that the quantum efficiency for two photon absorption should be refined at input average power that corresponds to a standard peak intensity of 1 GW/cm 2 with the repetition rate, the waist of focused beam, and the pulse width [4].…”
Section: Resultssupporting
confidence: 78%
See 1 more Smart Citation
“…For a GaP photodector, the maximum sensitivity for a one photon process was known to be Sone photon ~ 1 × 10 -1 mA/mW at 430 nm [24], which is three orders higher than that for the two photon process. The two photon sensitivity for the GaP photodiode is comparable to the previous report for GaAsP photodiode by the same order of magnitude [4,17]. Note that the quantum efficiency for two photon absorption should be refined at input average power that corresponds to a standard peak intensity of 1 GW/cm 2 with the repetition rate, the waist of focused beam, and the pulse width [4].…”
Section: Resultssupporting
confidence: 78%
“…Phase mismatch, in particular, can lead to a spectral-filtering effect to make a measured autocorrelation function significantly distorted. Several groups have demonstrated that TPA or 3PA based processes can be effective for pulse diagnostics in the femtosecond and picosecond time range with photodiodes using Si [2,3], GaAsP [2,[4][5][6][7], InGaAs [8], SiC [9,10], ZnSSe [11], GaN [12], light-emitting diodes using AlGaAs [13], laser diodes using GaAsP [3], GaAs/AlGaAs [14], GaN [15] and photocathodes using CsI and CuI PMTs [16] in autocorrelator schemes. Other semiconductor waveguides and microcavity structure devices were also developed [17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…The electric field of the Gaussian beam can be expressed in air as (1) is the wavenumber in vacuum, is the incident wavelength, is the position of the minimum beam waist, and are two orthogonal axes which are both orthogonal to which is the direction of propagation of the Gaussian beam, is the beam radius at , is the beam radius at . To calculate the field in the active layer which is sandwiched between two highly reflective Bragg mirrors, we decompose the field at the detector surface [ as shown in Fig.…”
Section: Theoretical Analysismentioning
confidence: 99%
“…T WO-PHOTON absorption (TPA) in semiconductors has recently received interest as it can be employed to characterize very short optical pulses, with characterization of optical pulses as short as 6 fs using TPA in GaAsP having been demonstrated [1]. TPA in silicon has been shown as a means of harvesting electrical energy using the two-photon photovoltaic effect [2].…”
Section: Introductionmentioning
confidence: 99%
“…The autocorrelation of pulses as short as 6 fs has been reported using a TPA photodetector [1]. Optical sampling and channel identification in optical telecommunications networks have also been demonstrated using TPA detectors [2,3].…”
mentioning
confidence: 99%